2018
DOI: 10.1186/s13550-018-0358-8
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of target-mediated uptake with immuno-PET: analysis of a phase I clinical trial with an anti-CD44 antibody

Abstract: BackgroundIdeally, monoclonal antibodies provide selective treatment by targeting the tumour, without affecting normal tissues. Therefore, antibody imaging is of interest, preferably in early stages of drug development. However, the imaging signal consists of specific, as well as non-specific, uptake. The aim of this study was to assess specific, target-mediated uptake in normal tissues, with immuno-PET in a phase I dose escalation study, using the anti-CD44 antibody RG7356 as example.ResultsData from thirteen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…89 Zr-labeled RG7356 was therefore further injected into monkeys as a cross-reactive species and revealed remarkably high uptake in the spleen 7 . A first-in-human trial of 89 Zr-labeled RG7356 in patients with solid malignancies also demonstrated high splenic uptake that required co-injection of excess cold Ab to achieve tumor targeting 8 , 9 . These previous studies indicate that radiolabeled Abs raised against the constant domain of CD44 protein of the host species accumulate to high levels in the spleen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…89 Zr-labeled RG7356 was therefore further injected into monkeys as a cross-reactive species and revealed remarkably high uptake in the spleen 7 . A first-in-human trial of 89 Zr-labeled RG7356 in patients with solid malignancies also demonstrated high splenic uptake that required co-injection of excess cold Ab to achieve tumor targeting 8 , 9 . These previous studies indicate that radiolabeled Abs raised against the constant domain of CD44 protein of the host species accumulate to high levels in the spleen.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, CD44 is a major marker of cancer stemness as characterized by self-renewal capacity, epithelial-mesenchymal transition, and treatment resistance 1 . CD44 thus provides an attractive target for cancer treatment 2 4 , and radiolabeled anti-CD44 antibodies (Abs) are being investigated for targeted imaging 5 9 , as well as radio-immunotherapy of solid tumors 10 , 11 .…”
Section: Introductionmentioning
confidence: 99%
“…In this review, we will describe in-depth some selected markers (i.e., CD20, CD38, CD146, and CD105). However, there are many other CD antigens that have shown potential as molecular imaging targets, including CD54 (known as intercellular adhesion molecule, ICAM-1), CD44, , CD47, and CD138. , …”
Section: Immunopet Imaging Of Cancersmentioning
confidence: 99%
“…High expression of CD40 in healthy organs might induce a sink effect that alters the antibody kinetics and atherosclerotic plaque targeting. In certain cases, a saturation of the sink organs can improve targeting to the organs of interest [22]. To investigate this, we evaluated the effect of a higher mass dose ("high dose" of 1000 µg) on the pharmacokinetics and aorta uptake of [ 89 Zr]Zr-anti-CD40 mAb in ApoE −/− mice.…”
Section: Ex Vivo Biodistribution and Blood Kinetics Of [ 89 Zr]zr-ant...mentioning
confidence: 99%